Medical comorbidities impact reimbursement rates in patients undergoing carpal tunnel release: an analysis of 76,996 patients - Madden, Michael; Motisi, Matthew; Wang, Christopher A.; Ameri, Bijan J.; Vakharia, Rushabh M.; Roche, Martin W. (Annals of Joint, 2018)
Background: Medical comorbidities have been shown to impact outcomes in patients with carpal tunnel syndrome (CTS) undergoing primary open carpal tunnel release (CTR). There is paucity in the literature comparing reimbursement rates of patients with medical comorbidities undergoing CTR compared to the general population. The study analyzed and compared reimbursements of medical comorbidities in patients undergoing open CTR. Methods: A retrospective review was performed using the PearlDiver supercomputer (PearlDiver Technologies, Fort Wayne, IN, USA). Patients were queried using International Classification of Disease, ninth revision (ICD-9) and Current Procedural Terminology (CPT) coding. Comorbidities analyzed included: obesity, chronic kidney disease (CKD), cirrhosis, chronic obstructive pulmonary disease (COPD), depression, diabetes mellitus, hypertension, hyperlipidemia, and smoking. Analysis of variance (ANOVA) was used to compare 90-day mean reimbursement rates. Tukey’s post-hoc testing was used to determine significance between the comorbidities and the general population. An alpha value less than 0.05 was considered statistically significant. Results: The query returned 76,996 patients who underwent primary CTR from 2007–2015. Mean total global 90-day episode of care reimbursement was $5,274 (range: $5,520–$7,193; SD: $663). ANOVA demonstrated statistical difference between comorbidities and the general population. Reimbursement rates were highest in patients with cirrhosis ($7,045) and lowest in patients with hyperlipidemia ($5,520). Reimbursement rates in the general population were $5,274. Conclusions: Comorbidities increase the total global 90-day episode of care costs amongst patients undergoing open CTR compared to the general population. Appropriate presurgical optimization could potentially minimize the costs associated with these conditions.